Ecce Agnus Dei: rezeptionsästhetische Untersuchung zum neutestamentlichen Gotteslamm in der bildenden Kunst - Lerdon, Saskia (Novum testamentum et orbis antiquus, 2020)
The Lamb of God has been a recurring motif in art history for two millennia. Saskia Lerdon investigates the impact of this christological metaphor on European art. Finding numerous examples within art history, she illustrates that this metaphor has been consistently reinterpreted and reconfigured in the artists’ historical situations. A key question is: Did new meanings develop in the course of this historical process beyond the original intentions of the authors of the New Testament? Hermeneutical theories such as those of Hans-Georg Gadamer help to analyse the material in addressing this question.